High School Socioeconomic Segregation and Student Attainment. (August 2013) - Palardy, Gregory J.
Using data from the Education Longitudinal Study of 2002, this study examines the association between high school socioeconomic segregation and student attainment outcomes and the mechanisms that mediate those relationships. The results show that socioeconomic segregation has a strong association with high school graduation and college enrollment. Controlling for an array of student and school factors, students who attend high socioeconomic composition (SEC) schools are 68% more likely to enroll at a 4-year college than students who attend low SEC schools. Two mediating mechanisms were examined, including socioeconomic-based peer influences and school effects. The results indicate the association between SEC and attainment is due more to peer influences, which tend to be negative in the low SEC setting. However, school practices that emphasize academics also play a major role, particularly in mediating the relationship between SEC and 4-year college enrollment. These findings suggest that integrating schools is likely necessary to fully addressing the negative consequences of attending a low SEC school.